2005
DOI: 10.1021/ja052595+
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and Chemical Formation of [Mn4IVO5(terpy)4(H2O)2]6+, in Relation with the Photosystem II Oxygen-Evolving Center Model [Mn2III,IVO2(terpy)2(H2O)2]3+

Abstract: To examine the real ability of the binuclear di-mu-oxo complex [Mn2(III,IV)O2(terpy)2(H2O)2]3+ (2) to act as a catalyst for water oxidation, we have investigated in detail its redox properties and that of its mononuclear precursor complex [Mn(II)(terpy)2]2+ (1) in aqueous solution. It appears that electrochemical oxidation of 1 allows the quantitative formation of 2 and, most importantly, that electrochemical oxidation of 2 quantitatively yields the stable tetranuclear Mn(IV) complex, [Mn4(IV)O5(terpy)4(H2O)2]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 37 publications
7
81
0
1
Order By: Relevance
“…For example, Collomb and co-workers observed that O 2 is produced from irradiated pH 3 aqueous solutions of [Ru(bipy) 3 ] 2+ and peroxodisulfate in the absence of any catalyst. [224] In that case, a chloroacetate buffer was used. The pH of the solution may thus play an important role.…”
Section: +mentioning
confidence: 99%
“…For example, Collomb and co-workers observed that O 2 is produced from irradiated pH 3 aqueous solutions of [Ru(bipy) 3 ] 2+ and peroxodisulfate in the absence of any catalyst. [224] In that case, a chloroacetate buffer was used. The pH of the solution may thus play an important role.…”
Section: +mentioning
confidence: 99%
“…The mechanism shown in Figure 5 (top) is the result of isotope labeling studies which show that under high concentrations of oxidant the oxygen produced contains minimal 18 O label from the solvent while at lower concentrations of oxidant a significant fraction of the product contains a single oxygen from the solvent and some of the evolved O 2 contains two oxygen from the solvent [93]. The fact that only oxygen-atom donor oxidants are functional has been a concern for this system [95], but recent results have shown that the catalyst is capable of oxygen evolution using Ce(IV) as an oxidant. Catalytic turnover is not attained when Ce(IV) is used as the oxidant due to the low pH required for use of Ce(IV) as an oxidant which causes deactivation of the catalyst [96].…”
Section: [(Tpy)(h 2 O)mn(o) 2 Mn(h 2 O)(tpy)] 3+ -mentioning
confidence: 99%
“…19a) was reported by Brudvig and coworkers to serve as the first model for catalytic O-O bond formation that employed typical oxidants such as sodium hypochlorite or KHSO 5 [152]. It has since been suggested that the dioxygen released comes about via a disproportionation reaction [153]. Collomb and coworkers explored this system via electrochemical methods [154,155].…”
Section: Proposed Catalytic Dinuclear Mn Modelsmentioning
confidence: 99%